Mineral and heavy metals content in tilapia fish (Oreochromis niloticus) collected from the River Nile in Damietta governorate, Egypt and evaluation of health risk from tilapia consumption - Abd El-Samee, Laila D; Hamouda, Yasser A; Hashish, Samia M; Abdel-Wahhab, Mosaad A (Comunicata Scientiae, 2019)
This study was conducted to determine heavy metals and trace elements content in tilapia fish collected from three sources in Damietta governorate, Egypt and to evaluate the human health risk due to tilapia consumption. Tilapia samples were collected from two locations in the River Nile stream, tow fish farms and two sluiceways. Health risk assessment was evaluated based on the consumption habits of adult human. The results revealed that all samples vary in elements concentrations. The calculation of human health risk revealed that the consumption of tilapia in the three tested area does not pose any health risk except for Selenium. It could be concluded that consumption of such fish may be a risk for consumers who eat fish more than one time per week. Consequently, precautions should be taken and warning against eating tilapia fish caught from these regions should be announced.